1985
DOI: 10.1126/science.3901258
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Switching of Colony Morphology in Candida albicans

Abstract: The pathogenic yeast Candida albicans switches heritably and at high frequency between at least seven general phenotypes identified by colony morphology on agar. Spontaneous conversion from the original smooth to variant phenotypes (star, ring, irregular wrinkle, hat, stipple, and fuzzy) occurs at a combined frequency of 1.4 X 10(-4), but is increased 200 times by a low dose of ultraviolet light that kills less than 10 percent of the cells. After the initial conversion, cells switch spontaneously to other phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
313
1
4

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(341 citation statements)
references
References 15 publications
13
313
1
4
Order By: Relevance
“…neoformans change their phenotypes when they are subcultured repeatedly or passaged in vivo [11][12][13][14][15][16]. C. albicans spontaneously switches the morphology of its colonies into at least seven general phenotypes [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neoformans change their phenotypes when they are subcultured repeatedly or passaged in vivo [11][12][13][14][15][16]. C. albicans spontaneously switches the morphology of its colonies into at least seven general phenotypes [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, clinically important fungi such as Candida albicans and Cryptococcus neoformans are known to change their phenotype after repeated subcultures or in-vivo passages [11][12][13][14][15][16]. This process is thought to allow some fungi to escape eradication by the host immune system [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The electrophoretic karyotype of 1006 is the one most frequently found in clinical isolates. WO-1 (Slutsky et al 1985) was shown by Chu et al (1993) to have several reciprocal translocations, including one involving chromosome 7. Iwaguchi et al (1990) selected ten strains showing chromosome length polymorphism (CLP) from 50 clinical strains in Nagoya, Japan.…”
Section: Methods Strainsmentioning
confidence: 99%
“…For fungi phenotypic switching is defined as the reversible change manifested as altered colony morphology at a rate higher than the somatic mutation rate. Phenotypic switching has been reported first in Candida over 20 years ago [2,3] and the molecular mechanism has been studied extensively [4,5]. In Candida phenotypic switching controls mating and has also been proposed to contribute to virulence [6].…”
Section: Introductionmentioning
confidence: 99%